Snake‐Inspired, Nano‐Stepped Surface with Tunable Frictional Anisotropy Made from a Shape‐Memory Polymer for Unidirectional Transport of Microparticles. (28th February 2021) - Wu, Weibin; Guttmann, Markus; Schneider, Marc; Thelen, Richard; Worgull, Matthias; Gomard, Guillaume; Hölscher, Hendrik
Abstract: The ventral scales of many snake species are decorated with oriented micro‐fibril structures featuring nano‐steps to achieve anisotropic friction for efficient locomotion. Here, a nano‐stepped surface with tunable frictional anisotropy inspired by this natural structure is presented. It is fabricated by replicating the micro‐fibril structure of the ventral scales of the Chinese cobra ( Naja atra ) into a thermo‐responsive shape‐memory polymer via hot embossing. The resulting smart surface transfers from a flat topography to a predefined structure of nano‐steps upon heating. During this recovery process, the nano‐steps grow out of the surfaces resulting in a surface with frictional anisotropy, which is characterized in situ by an atomic force microscopy. The desired frictional anisotropy can be customized by stopping the heating process before full recovery. The nano‐stepped surface is employed for the unidirectional transport of microscale particles through small random vibrations. Due to the frictional anisotropy, the microspheres drift unidirectionally (down the nano‐steps). Finally, dry self‐cleaning is demonstrated by the transportation of a pile of microparticles. Abstract : A nano‐stepped surface with frictional anisotropy inspired by snake scales is replicated into a thermo‐responsive shape‐memory polymer. The resulting smart surface has a tunable frictional anisotropy, is transparent, and allows the unidirectional transport of microscale particles through small random vibrations. This effect can be utilized for dry self‐cleaning of technical surfaces like solar modules.